Numerical Investigation on the Anti-Angiogenic Therapy-Induced Normalization in Solid Tumors - Mahya Mohammadi; Cyrus Aghanajafi; M. Soltani; Kaamran Raahemifar (Pharmaceutics, 2022)
This study numerically analyzes the fluid flow and solute transport in a solid tumor to comprehensively examine the consequence of normalization induced by anti-angiogenic therapy on drug delivery. The current study leads to a more accurate model in comparison to previous research, as it incorporates a non-homogeneous real-human solid tumor including necrotic, semi-necrotic, and well-vascularized regions. Additionally, the model considers the effects of concurrently chemotherapeutic agents (three macromolecules of <semantics>IgG</semantics>, <semantics>F(ab′)2</semantics>, and <semantics>F(ab′)</semantics>) and different normalization intensities in various tumor sizes. Examining the long-term influence of normalization on the quality of drug uptake by necrotic area is another contribution of the present study. Results show that normalization decreases the interstitial fluid pressure (IFP) and spreads the pressure gradient and non-zero interstitial fluid velocity (IFV) into inner areas. Subsequently, wash-out of the drug from the tumor periphery is decreased. It is also demonstrated that normalization can improve the distribution of solute concentration in the interstitium. The efficiency of normalization is introduced as a function of the time course of perfusion, which depends on the tumor size, drug type, as well as normalization intensity, and consequently on the dominant mechanism of drug delivery. It is suggested to accompany anti-angiogenic therapy by <semantics>F(ab′)</semantics> in large tumor size (<semantics>Req=2.79 cm</semantics>) to improve reservoir behavior benefit from normalization. However, <semantics>IgG</semantics> is proposed as the better option in the small tumor (<semantics>Req=0.46 cm</semantics>), in which normalization finds the opportunity of enhancing uniformity of <semantics>IgG</semantics> average exposure by 22%. This study could provide a perspective for preclinical and clinical trials on how to take advantage of normalization, as an adjuvant treatment, in improving drug delivery into a non-homogeneous solid tumor.